2017
DOI: 10.15567/mljekarstvo.2017.0407
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calving season on reproductive performance of Jersey cows

Abstract: Dairy records, containing 1269 lactation record of 462 Jersey dairy cows collected over 16 years, from an agricultural state farm were used. Data for reproductive performance of cows were also collected. Means of the herd for lactation milk yield, calving interval, days open, interval from calving to the first insemination, lactation length, gestation length and dry period were 3195.7±20.2 kg, 366.6±1.7 d, 92.9±1.6 d, 78.0±1.3 d, 301.7±1.1 d, 275.2±0.2 d and 69.3±0.8 d, respectively. The effect of calving seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
2
5
0
1
Order By: Relevance
“…These findings have confirmed the estimates of survival functions generated by the Kaplan-Meier method (Table 4), where the medians of days open for all seasons were shorter than those of summer. These findings agreed with the reports of other researchers (Farin et al, 1994;Muller et al, 2014;Soydan and Kuran, 2017) who concluded that high temperatures and heat stress adversely affect the reproductive efficiency of dairy cattle. In practice, it can be concluded that, cows calved in winter had a 36.7 % higher hazard of conception than cows calved in summer.…”
Section: Cox Phr Model and Semi-parametric Survival Estimatessupporting
confidence: 93%
See 1 more Smart Citation
“…These findings have confirmed the estimates of survival functions generated by the Kaplan-Meier method (Table 4), where the medians of days open for all seasons were shorter than those of summer. These findings agreed with the reports of other researchers (Farin et al, 1994;Muller et al, 2014;Soydan and Kuran, 2017) who concluded that high temperatures and heat stress adversely affect the reproductive efficiency of dairy cattle. In practice, it can be concluded that, cows calved in winter had a 36.7 % higher hazard of conception than cows calved in summer.…”
Section: Cox Phr Model and Semi-parametric Survival Estimatessupporting
confidence: 93%
“…The results revealed that cows calved in winter months had shorter DO than those calved in summer and hot months. This finding is in consistence with those reported by other studies (Muller et al, 2014;Soydan and Kuran, 2017) who revealed that cows that calved in winter months had more chance to become pregnant than those calved in summer. Jordan (2003) reported that when dairy cows are exposed to heat stress, their reproductive performance declines along with uncontrolled estrus.…”
Section: Kaplan-meier Curves and Nonparametric Survival Estimatessupporting
confidence: 92%
“…We deduce that there was low protein intake in some farms from our low mean PE ratio and that protein deficiency, especially in early lactation, had an impact on the reproductive efficiency [16,17]. Prolonged days open, increased number of services per conception, and decreased pregnancy rate have been reported problems associated with inadequate protein intake elsewhere [16,18].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, summer months have been shown to lead to reproductive hormone disturbance, deteriorated oocyte development, and early fetal death [19]. In addition to these direct effects of high temperature on reproduction, summer months have also been shown to indirectly influence reproduction by low protein and digestibility in the pasture and decreased feed intake, resulting in a negative change in energy balance [18,22]. Our results slightly differed from these seasonal effects on FSC during 4 months after calving; there was no significant difference in FSC between the rainy season and summer season in our data.…”
Section: Discussionmentioning
confidence: 99%
“…A lucratividade do sistema de produção de bovinos de corte está intimamente relacionada com a eficiência reprodutiva do rebanho. No Brasil, ainda são registradas baixas taxas de eficiência reprodutiva, devido a mortalidade embrionárias, que promovem longos intervalos de partos e baixa lucratividade aos sistemas de produção de carne bovina (Soydan & Kuran, 2017;Silva et al 2019).…”
Section: Introductionunclassified